Fetal body MRI and its application to fetal and neonatal treatment: an illustrative review. (June 2021) - Davidson, Joseph R; Uus, Alena; Matthew, Jacqueline; Egloff, Alexia M; Deprez, Maria; Yardley, Iain; De Coppi, Paolo; David, Anna; Carmichael, Jim; Rutherford, Mary A
Summary: This Review depicts the evolving role of MRI in the diagnosis and prognostication of anomalies of the fetal body, here including head and neck, thorax, abdomen and spine. A review of the current literature on the latest developments in antenatal imaging for diagnosis and prognostication of congenital anomalies is coupled with illustrative cases in true radiological planes with viewable three-dimensional video models that show the potential of post-acquisition reconstruction protocols. We discuss the benefits and limitations of fetal MRI, from anomaly detection, to classification and prognostication, and defines the role of imaging in the decision to proceed to fetal intervention, across the breadth of included conditions. We also consider the current capabilities of ultrasound and explore how MRI and ultrasound can complement each other in the future of fetal imaging.